Assessment of spring water quality and people's perception on the springs in Goenkhatoed Gewog, Gasa Dzongkhag - Yeshi Jamtsho (CNR, Lobesa Yeshi Jamtsho, 2022)
includes acknowledgement and abstract
Keywords: Thesis